Electroplating method and electroplating material for steel-titanium material
By using HT-57 titanium surface adjustment and HT-79W titanium special pre-plating nickel on the surface of titanium and stainless steel or iron composite materials, combined with a multi-step electroplating process, the problem of poor binding force of titanium and stainless steel or iron composite materials is solved, and the coating binding force is significantly improved and the application range is expanded.
Patent Information
- Application Number
- CN202411890953.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-08
AI Technical Summary
The binding force of titanium and stainless steel or iron composite materials is unstable during electroplating, especially when plating thicker nickel and harder chromium layers, resulting in abnormal quality.
The HT-57 titanium surface adjustment and HT-79W titanium special pre-plating nickel is used to form a film layer and increase the bonding force between the titanium substrate and the plating layer. Through a multi-step electroplating process, including chemical polishing, sand blasting, ultrasonic oil removal, cathode electrolysis oil removal, acid corrosion, surface adjustment, pre-plating, semi-gloss nickel electroplating, gloss nickel electroplating, chromium electroplating and high-temperature baking treatment, the stable water electroplating of titanium and stainless steel or iron composite materials is achieved.
The coating bonding force between titanium and stainless steel or iron composite materials has been significantly improved, the problem of poor coating bonding force has been solved, and the application range has been expanded.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to an electroplating method for steel-titanium materials and electroplating materials, belonging to the technical field of metal water electroplating surface treatment. Background Art
[0002] There are many composite materials in the existing golf club heads. There are composite materials of stainless steel and tungsten, stainless steel and iron, stainless steel and copper, stainless steel and nickel-iron, and recently, stainless steel and titanium alloy composite materials. The bonding strength of the electroplated layer of titanium alloy is not very stable, especially when plating thicker nickel layers and harder chromium layers, the quality of poor bonding strength of the plating layer often occurs. Now there are products with stainless steel and copper brazing and titanium alloy composite structures, and the bonding strength of the water electroplated layer is even more unstable. In order to solve the above problems, a water electroplating process for iron and titanium alloy composites and stainless steel and titanium alloy composites has been developed. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for electroplating a steel-titanium material and an electroplating material to solve the problem that titanium is not easy to electroplate with water when it is combined with stainless steel or iron.
[0004] The present invention is achieved through the following technical solutions: A method for electroplating a steel-titanium material, characterized in that the method comprises the following steps: 1.1 Chemical polishing treatment, use HT-678 chemical polishing agent, the dosage is 200-300ml / L, the processing temperature is 20-40℃, and the chemical polishing time is 1-2 minutes; 1.2 Sand blasting, using 240# aluminum oxide sand to remove burrs and oxide film from the material and increase surface roughness; 1.3 Ultrasonic degreasing treatment, use HT-35F titanium degreasing agent, the dosage is 80-100g / L, the temperature is 50-60℃, and the time is 5-10 minutes; 1.4 Cathodic electrolytic degreasing treatment, use HT-35FA titanium degreasing agent, dosage is 60-80g / L, temperature is 50-60℃, current density is 1-4A / dm², time is 1-3 minutes; 1.5 Acid etching treatment, use 68% nitric acid 100-150ml / L and 40% hydrofluoric acid 100-200ml / L, the treatment time is 30-60 seconds at room temperature; 1.6 Surface conditioning treatment: use HT-57 titanium surface conditioning agent, the dosage is 200-400ml / L, the temperature is 40℃-50℃, and the time is 10-25 seconds; 1.7 Pre-nickel plating treatment, use HT-79W titanium special pre-nickel plating, the dosage of agent A is 500-620ml / L, the dosage of agent B is 100-200ml / L, the temperature is 50-65℃, the pH value is 2.0-2.7, the time is 2-8 minutes, and the cathode current density is 2-5A / dm²; 1.8 Semi-gloss nickel electroplating treatment, the electroplating solution is composed of nickel sulfate, nickel chloride and boric acid, the concentration of nickel sulfate is 200-300g / L, the concentration of nickel chloride is 40-60g / L, the concentration of boric acid is 45-50g / L, the cathode current density is 2-3A / dm², the pH value is 3.8-4.2, the temperature is 45-50℃, and the electroplating time is 5-30 minutes; 1.9 Glossy nickel electroplating treatment, the electroplating solution is composed of nickel sulfate, nickel chloride, and boric acid, the concentration of nickel sulfate is 200-280g / L, the concentration of nickel chloride is 45-60g / L, the concentration of boric acid is 45-50g / L, the pH value is 4.4, the temperature is 50℃-60℃, the time is 10-30 minutes, and the cathode current density is 2.5A / dm²; 1.10 Chromium electroplating treatment, the electroplating solution is composed of chromic acid, acid radical, and trivalent chromium, the chromic acid concentration is 300-400g / L, the acid radical concentration is 3.0-3.5g / L, the trivalent chromium concentration is 2-5g / L, the temperature is 60℃, the cathode current density is 25A / dm², and the time is 10-50 minutes; 1.11 High temperature baking treatment, temperature is 350℃, time is 3 hours, and then naturally cool.
[0005] The electroplating method as described above is characterized in that in the chemical polishing process, the dosage of HT-678 chemical polishing agent is 250 ml / L, the processing temperature is 30° C., and the chemical polishing time is 1 minute.
[0006] The electroplating method as described above is characterized in that: the dosage of the HT-57 titanium material surface conditioner is preferably 300 ml / L, the temperature is 40° C., and the time is 20 seconds.
[0007] The electroplating method as described above is characterized in that: the dosage of agent A of the HT-79W titanium material special pre-nickel plating is preferably 500ml / L, the dosage of agent B is preferably 200ml / L, the pH value is 2.5, the time is 5 minutes, and the cathode current density is 3A / dm².
[0008] The electroplating method as described above is characterized in that: in the cathode electrolytic degreasing treatment process, the amount of HT-35FA titanium material degreasing agent is 80g / L, the temperature is 60°C, the current density is 3A / dm2, and the time is 2 minutes; The electroplating method as described above is characterized in that: in the semi-gloss nickel electroplating treatment process, the amount of commercially available semi-gloss nickel bath building agent MU is 6-10 ml / L, preferably 8 ml / L, the amount of semi-gloss nickel gloss agent is 0.3-0.5 ml / L, preferably 0.4 ml / L, and the amount of wetting agent is 0.4-1.0 ml / L, preferably 0.5 ml / L.
[0009] The electroplating method as described above is characterized in that: in the glossy nickel electroplating treatment process, the amount of commercially available nickel gloss agent used is 0.4-0.6 ml / L, preferably 0.4 ml / L; the amount of nickel softener used is 6-10 ml / L, preferably 8 ml / L; the amount of nickel wetting agent used is 0.6-0.8 ml / L, preferably 0.8 ml / L.
[0010] The electroplating method as described above is characterized in that the amount of the chromium additive in the chromium electroplating solution is 20-30 ml / L, preferably 25 ml / L.
[0011] The electroplating method as described above is characterized in that in the ultrasonic degreasing treatment process, the dosage of HT-35F titanium degreasing agent is 60°C, the current density is 3A / dm2, and the time is 2 minutes; in the acid etching treatment process, 68% nitric acid is 100 ml / liter, 40% hydrofluoric acid is 150 ml / liter, and the room temperature treatment time is 30 seconds.
[0012] An electroplating material, characterized in that the steel-titanium composite material is prepared by the electroplating method as described above.
[0013] Compared with the prior art, the present invention has the following advantages: The present invention first uses HT-57 titanium surface conditioner to produce a film layer on the surface of the steel-titanium composite material, and then uses HT-79W titanium material special pre-plating nickel pre-plating to increase the bonding force between the titanium substrate and the subsequent plating layer, completing the water electroplating process flow of the titanium and stainless steel or iron composite material in a true sense. Thus, the problem of poor bonding force caused by the electroplating of nickel and chromium on titanium and stainless steel or iron composite materials in the past is solved, and the application is not limited to golf club heads, and the application range is wide. DETAILED DESCRIPTION
[0014] The technical features of the present invention are further described below in detail so that those skilled in the art can understand them.
[0015] The present invention includes the following implementation process: 1. Chemical polishing 2. Sand blasting 3. Ultrasonic degreasing treatment 4. Electrolytic degreasing treatment 5. Table adjustment processing 6. Acid etching 7. Pre-nickel plating 8. Semi-bright nickel plating 9.Glossy Nickel Plating 10. Chrome plating 11. High temperature baking treatment The electroplating method of the titanium and stainless steel or iron composite material of the present invention can make the bonding force between the composite substrate and the coating excellent. The present invention is further described below in conjunction with examples: The first implementation example is a golf club head A made of a composite material of titanium and stainless steel.
[0016] The second implementation example is a golf club head B made of a composite material of titanium and stainless steel.
[0017] The third implementation example is a golf club head C made of a composite material of titanium and iron.
[0018] The fourth implementation example is a golf club head D made of a composite material of titanium and iron.
[0019] Implementation Case 1 (1) Chemical polishing treatment: Use HT-678 chemical polishing agent, 250ml / L, processing temperature is 30℃, polishing time is 1 minute. Remove surface dirt and oxide film to make the surface of the material cleaner.
[0020] (2) Sand blasting: The steel-titanium composite material after the treatment in step (1) is treated with 240 aluminum oxide sand to remove burrs, oxide films, etc. generated by the material itself during the die-casting process and increase the surface roughness.
[0021] (3) Ultrasonic degreasing treatment: The steel-titanium composite material treated in step (2) was degreased using the product HT-35F titanium material degreaser, with an initial concentration of 80 g / L, a temperature of 50°C, and a time of 5 min.
[0022] (4) Cathodic electrolytic degreasing treatment: The steel-titanium composite material treated in step (3) is subjected to cathodic electrolysis degreasing. The cathodic electrolysis uses the product HT-35F titanium material degreasing agent, with an initial concentration of 60 g / L, a temperature of 60°C, an anode current density of 4 A / dm2, and a time of 90 seconds. (5) Acid etching The surface of the steel-titanium composite material treated in step (4) is defilmed using a defilming solution of 100 ml / L nitric acid and 200 ml / L hydrofluoric acid at room temperature for 30 seconds.
[0023] (6) Table adjustment processing The steel-titanium composite material treated in step (5) was subjected to HT-57 titanium material surface conditioning at 200 ml / L at a temperature of 40° C. for 10 seconds.
[0024] (7) Pre-nickel plating The titanium alloy treated in step (6) was pre-plated. The pre-plating solution used was HT-79W titanium material special pre-nickel plating solution. The dosage of agent A was 500 ml / L, the dosage of agent B was 200 ml / L, the temperature was 60°C, the pH value was 2.0, the time was 5 minutes, and the cathode current density was 2 A / dm2.
[0025] (8) Semi-gloss nickel plating treatment: The titanium alloy treated in step (7) was subjected to semi-bright nickel electroplating. The composition of the electroplating solution was 240 g / L nickel sulfate, 50 g / L nickel chloride, 45 g / L boric acid, pH value was 3.8, temperature was 50°C, time was 20 min, anode current density was 2 A / dm2, and commercially available semi-bright nickel bath building agent MU 8 ml / L, semi-bright nickel gloss agent 0.4 ml / L, and wetting agent 0.5 ml / L were used.
[0026] (9) Glossy nickel plating treatment: The titanium alloy treated in step (8) was subjected to bright nickel electroplating. The composition of the electroplating solution was 220 g / L nickel sulfate, 45 g / L nickel chloride, 50 g / L boric acid, pH 4.4, temperature 55°C, time 10 min, anode current density 2.5 A / dm2, and commercially available nickel brightener 810 0.4 ml / L, nickel softener 8 ml / L, and nickel wetting agent 0.5 ml / L.
[0027] (10) Chrome plating treatment: The titanium alloy treated in step (9) was subjected to chromium electroplating. The composition of the electroplating solution was 350 g / L chromic acid, 3.0 g / L acid radical, 3 g / L trivalent chromium, the temperature was 60°C, the anode current density was 25 A / dm2, the time was 15 min, and 20 ml / L of commercially available chromium additive was used.
[0028] Pure water is used for washing between the above steps, and product A is obtained through the above treatment.
[0029] (11) High temperature baking treatment: 350 degrees, 3 hours, remove and cool naturally.
[0030] Implementation Case 2 (1) Chemical polishing treatment: Use HT-678 chemical polishing agent, 300ml / L, processing temperature is 40℃, polishing time is 1.5 minutes. Remove surface dirt and oxide film to make the surface of the material cleaner.
[0031] (2) Sand blasting: The steel-titanium composite material after the treatment in step (1) is treated with 240 aluminum oxide sand to remove burrs, oxide films, etc. generated by the material itself during the die-casting process and increase the surface roughness.
[0032] (3) Ultrasonic degreasing treatment: The steel-titanium composite material treated in step (2) was degreased using the product HT-35F titanium material degreaser, with an initial concentration of 80 g / L, a temperature of 50°C, and a time of 5 min.
[0033] (4) Cathodic electrolytic degreasing treatment: The steel-titanium composite material treated in step (3) is subjected to cathodic electrolysis degreasing. The cathodic electrolysis uses the product HT-35F titanium material degreasing agent, with an initial concentration of 60 g / L, a temperature of 60°C, an anode current density of 4 A / dm2, and a time of 90 seconds. (5) Acid etching The surface of the steel-titanium composite material treated in step (4) is defilmed using a defilming solution of 150 ml / L nitric acid and 150 ml / L hydrofluoric acid at room temperature for 30 seconds.
[0034] (6) Table adjustment processing The steel-titanium composite material treated in step (5) was subjected to HT-57 titanium material surface conditioning at 300 ml / L at a temperature of 45° C. for 25 seconds.
[0035] (7) Pre-nickel plating The titanium alloy treated in step (6) was pre-plated. The pre-plating solution used was HT-79W titanium material special pre-nickel plating solution. The dosage of agent A was 500 ml / L, the dosage of agent B was 200 ml / L, the temperature was 60°C, the pH value was 2.5, the time was 4 minutes, and the cathode current density was 3 A / dm2.
[0036] (8) Semi-gloss nickel plating treatment: The titanium alloy treated in step (7) was subjected to semi-bright nickel electroplating. The composition of the electroplating solution was 240 g / L nickel sulfate, 50 g / L nickel chloride, 45 g / L boric acid, pH value was 3.8, temperature was 50°C, time was 20 min, anode current density was 2 A / dm2, and commercially available semi-bright nickel bath building agent MU 8 ml / L, semi-bright nickel gloss agent 0.4 ml / L, and wetting agent 0.5 ml / L were used.
[0037] (9) Glossy nickel plating treatment: The titanium alloy treated in step (8) was subjected to bright nickel electroplating. The composition of the electroplating solution was 220 g / L nickel sulfate, 45 g / L nickel chloride, 50 g / L boric acid, pH 4.4, temperature 55°C, time 10 min, anode current density 2.5 A / dm2, and commercially available nickel brightener 810 0.4 ml / L, nickel softener 8 ml / L, and nickel wetting agent 0.5 ml / L.
[0038] (10) Chrome plating treatment: The titanium alloy treated in step (9) was subjected to chromium electroplating. The composition of the electroplating solution was 350 g / L chromic acid, 3.0 g / L acid radical, 3 g / L trivalent chromium, the temperature was 60°C, the anode current density was 25 A / dm2, the time was 15 min, and 20 ml / L of commercially available chromium additive was used.
[0039] Pure water is used for washing between the above steps, and product B is obtained through the above treatment.
[0040] (11) High temperature baking treatment: 350 degrees, 3 hours, remove and cool naturally.
[0041] Implementation Case 3 (1) Chemical polishing treatment: Use HT-678 chemical polishing agent, preferably 230ml / L, processing temperature is 20℃, polishing time is 2 minutes. Remove surface dirt and oxide film to make the surface of the material cleaner.
[0042] (2) Sand blasting: The steel-titanium composite material after the treatment in step (1) is treated with 240 aluminum oxide sand to remove burrs, oxide films, etc. generated by the material itself during the die-casting process and increase the surface roughness.
[0043] (3) Ultrasonic degreasing treatment: The steel-titanium composite material treated in step (2) was degreased using the product HT-35F titanium degreaser, with an initial concentration of 100 g / L, a temperature of 50°C, and a time of 8 min.
[0044] (4) Cathodic electrolytic degreasing treatment: The steel-titanium composite material treated in step (3) is subjected to cathodic electrolysis degreasing. The cathodic electrolysis uses the product HT-35F titanium material degreasing agent, the starting concentration is 80g / L, the temperature is 60°C, the anode current density is 3A / dm2, and the time is 90 seconds. (5) Acid etching The surface of the steel-titanium composite material treated in step (4) is defilmed using a defilming solution of 100 ml / L nitric acid and 200 ml / L hydrofluoric acid at room temperature for 40 seconds.
[0045] (6) Table adjustment processing The steel-titanium composite material treated in step (5) was subjected to HT-57 titanium material surface conditioning at 400 ml / L at a temperature of 50° C. for 15 seconds.
[0046] (7) Pre-nickel plating The titanium alloy treated in step (6) was pre-plated. The pre-plating solution used was HT-79W titanium material special pre-nickel plating solution. The dosage of agent A was 550 ml / L, the dosage of agent B was 150 ml / L, the temperature was 60°C, the pH value was 2.0, the time was 5 minutes, and the cathode current density was 2 A / dm2.
[0047] (8) Semi-gloss nickel plating treatment: The titanium alloy treated in step (7) was subjected to semi-bright nickel electroplating. The composition of the electroplating solution was 240 g / L nickel sulfate, 50 g / L nickel chloride, 45 g / L boric acid, pH value was 3.8, temperature was 50°C, time was 20 min, anode current density was 2 A / dm2, and commercially available semi-bright nickel bath building agent MU 8 ml / L, semi-bright nickel gloss agent 0.4 ml / L, and wetting agent 0.5 ml / L were used.
[0048] (9) Glossy nickel plating treatment: The titanium alloy treated in step (8) was subjected to bright nickel electroplating. The composition of the electroplating solution was 220 g / L nickel sulfate, 45 g / L nickel chloride, 50 g / L boric acid, pH 4.4, temperature 55°C, time 10 min, anode current density 2.5 A / dm2, and commercially available nickel brightener 810 0.4 ml / L, nickel softener 8 ml / L, and nickel wetting agent 0.5 ml / L.
[0049] (10) Chrome plating treatment: The titanium alloy treated in step (9) was subjected to chromium electroplating. The composition of the electroplating solution was 350 g / L chromic acid, 3.0 g / L acid radical, 3 g / L trivalent chromium, the temperature was 60°C, the anode current density was 25 A / dm2, the time was 15 min, and 20 ml / L of commercially available chromium additive was used.
[0050] Pure water is used for washing between the above steps, and product C is obtained through the above treatment.
[0051] (11) High temperature baking treatment: 350 degrees, 3 hours, remove and cool naturally.
[0052] Implementation Case 4 (1) Chemical polishing treatment: Use HT-678 chemical polishing agent, preferably 280ml / L, processing temperature is 30℃, polishing time is 1 minute. Remove surface dirt and oxide film to make the surface of the material cleaner.
[0053] (2) Sand blasting: The steel-titanium composite material after the treatment in step (1) is treated with 240 aluminum oxide sand to remove burrs, oxide films, etc. generated by the material itself during the die-casting process and increase the surface roughness.
[0054] (3) Ultrasonic degreasing treatment: The steel-titanium composite material treated in step (2) was degreased using the product HT-35F titanium material degreaser, with an initial concentration of 80 g / L, a temperature of 50°C, and a time of 5 min.
[0055] (4) Cathodic electrolytic degreasing treatment: The steel-titanium composite material treated in step (3) is subjected to cathodic electrolysis degreasing. The cathodic electrolysis uses the product HT-35F titanium material degreasing agent, with an initial concentration of 60 g / L, a temperature of 60°C, an anode current density of 4 A / dm2, and a time of 90 seconds. (5) Acid etching The surface of the steel-titanium composite material treated in step (4) is defilmed using a defilming solution of 100 ml / L nitric acid and 200 ml / L hydrofluoric acid at room temperature for 30 seconds.
[0056] (6) Table adjustment processing The steel-titanium composite material treated in step (5) was subjected to HT-57 titanium material surface conditioning at 200 ml / L at a temperature of 40° C. for 10 seconds.
[0057] (7) Pre-nickel plating The titanium alloy treated in step (6) was pre-plated. The pre-plating solution used was HT-79W titanium material special pre-nickel plating solution. The dosage of agent A was 500 ml / L, the dosage of agent B was 200 ml / L, the temperature was 60°C, the pH value was 2.0, the time was 5 minutes, and the cathode current density was 2 A / dm2.
[0058] (8) Semi-gloss nickel plating treatment: The titanium alloy treated in step (7) was subjected to semi-bright nickel electroplating. The composition of the electroplating solution was 240 g / L nickel sulfate, 50 g / L nickel chloride, 45 g / L boric acid, pH value was 3.8, temperature was 50°C, time was 20 min, anode current density was 2 A / dm2, and commercially available semi-bright nickel bath building agent MU 8 ml / L, semi-bright nickel gloss agent 0.4 ml / L, and wetting agent 0.5 ml / L were used.
[0059] (9) Glossy nickel plating treatment: The titanium alloy treated in step (8) was subjected to bright nickel electroplating. The composition of the electroplating solution was 220 g / L nickel sulfate, 45 g / L nickel chloride, 50 g / L boric acid, pH 4.4, temperature 55°C, time 10 min, anode current density 2.5 A / dm2, and commercially available nickel brightener 810 0.4 ml / L, nickel softener 8 ml / L, and nickel wetting agent 0.5 ml / L.
[0060] (10) Chrome plating treatment: The titanium alloy treated in step (9) was subjected to chromium electroplating. The composition of the electroplating solution was 350 g / L chromic acid, 3.0 g / L acid radical, 3 g / L trivalent chromium, the temperature was 60°C, the anode current density was 25 A / dm2, the time was 15 min, and 20 ml / L of commercially available chromium additive was used.
[0061] Pure water is used for washing between the above steps, and product D is obtained through the above treatment.
[0062] (11) High temperature baking treatment: 350 degrees, 3 hours, remove and cool naturally.
[0063] Test method: Products A, B, C, and D were subjected to the hundred-grid knife test and the sandblasting test. The test results are shown in Table M.
[0064] Test Standard: (1) 100-grid knife test: Test standard: ISO 2409.
[0065] Test steps: Use a commercially available 1mmx11mm grid cutter to cut small squares horizontally and vertically, use 3M600 or 610 tape to stick on the grid, quickly pull up the 3M tape, and observe the size of the peeling area of the small squares.
[0066] Acceptance Criteria: For Grade 0 and Grade 1 acceptance, no angle lifting or enlargement is allowed for a cross-scratch.
[0067] ISO grade: 0 = ASTM grade 5B: Grade 0: The cut edge is completely smooth and there is no peeling on the lattice edge.
[0068] ISO grade: 1 = ASTM grade 4B: Grade 1: The peeling area in the cross-cut area shall not exceed 5%.
[0069] ISO Grade: 2 = ASTM Grade 3B: Grade 2: The peeling area of the cross-cut area is greater than 5%, but not more than 15%.
[0070] ISO Grade: 3 = ASTM Grade 2B: Grade 3: The peeling area of the cross-cut area is greater than 15%, but not more than 35%.
[0071] ISO Grade: 4 = ASTM Grade 1B: Grade 4: The peeling area of the cross-cut area is greater than 35%, but not more than 65%.
[0072] (2) Sandblasting test (Table M): Test standard: Use 100# alumina sand, sandblasting machine pressure 5.5 kg, at any selected area on the product, the sandblasting machine nozzle is 12 cm away from the selected area, spray the coating until the material is visible, and there is no blistering or peeling of the coating on the selected area.
[0073] Table M It can be seen from Table M that the products of the four implementation cases of the present invention all meet the requirements. The titanium and stainless steel or iron composite material adopts HT-57 titanium surface conditioner and HT-79W titanium special pre-plating. The combined process can make the nickel-chromium plating layer have good bonding strength with the composite substrate.
[0074] The embodiments described in the present invention are merely descriptions of the preferred implementation schemes of the present invention, and are not intended to limit the concept and scope of the invention. Without departing from the design of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should all fall within the protection scope of the present invention.
[0075] The embodiments described in the present invention are merely descriptions of the preferred implementation modes of the present invention, and are not intended to limit the concept and scope of the invention. Without departing from the design concept of the present invention, various modifications and improvements made to the technical solutions of the present invention by engineers and technicians in this field should all fall within the protection scope of the present invention.
Claims
1. A method for electroplating steel and titanium materials, characterized in that The electroplating method comprises the following steps: pre-treatment, surface conditioning treatment, pre-nickel plating treatment, and electroplating decorative coating; the surface conditioning treatment adopts HT-57 titanium surface conditioning agent, the dosage is 200-400ml / L, the temperature is 40℃-50℃, and the time is 10-25 seconds; the pre-nickel plating treatment adopts HT-79W titanium material special pre-nickel plating agent, the dosage of agent A is 500-620ml / L, the dosage of agent B is 100-200ml / L, the temperature is 50-65℃, the pH value is 2.0-2.7, the time is 2-8 minutes, and the cathode current density is 2-5A / dm².
2. The electroplating method according to claim 1, characterized in that the pre-treatment comprises the following steps in sequence: 2.1 Chemical polishing treatment, use HT-678 chemical polishing agent, the dosage is 200-300ml / L, the processing temperature is 20-40℃, and the chemical polishing time is 1-2 minutes; 2.2 Sand blasting, using 240# aluminum oxide sand to remove burrs and oxide films generated by the material itself during the die-casting process; 2.3 Ultrasonic degreasing treatment, use HT-35F titanium degreasing agent, the dosage is 80-100g / L, the temperature is 50-60℃, and the time is 5-10 minutes; 2.4 Cathodic electrolytic degreasing treatment, use HT-35FA titanium degreasing agent, the dosage is 60-80g / L, the temperature is 50-60℃, the current density is 1-4A / dm², and the time is 1-3 minutes; 2.5 Acid etching: use 68% nitric acid 100-150ml / L and 40% hydrofluoric acid 100-200ml / L, and the treatment time is 30-60 seconds at room temperature.
3. The electroplating method according to claim 1, characterized in that The electroplating decorative coating comprises the following steps in sequence: 3.1 Semi-gloss nickel electroplating treatment, the electroplating solution is composed of nickel sulfate, nickel chloride and boric acid, the concentration of nickel sulfate is 200-300g / L, the concentration of nickel chloride is 40-60g / L, the concentration of boric acid is 45-50g / L, the cathode current density is 2-3A / dm², the pH value is 3.8-4.2, the temperature is 45-50℃, and the electroplating time is 5-30 minutes; 3.2 Glossy nickel electroplating treatment, the electroplating solution is composed of nickel sulfate, nickel chloride, and boric acid, the concentration of nickel sulfate is 200-280g / L, the concentration of nickel chloride is 45-60g / L, the concentration of boric acid is 45-50g / L, the pH value is 4.4, the temperature is 50℃-60℃, the time is 10-30 minutes, and the cathode current density is 2.5A / dm²; 3.3 Chromium electroplating treatment, the plating solution is composed of chromic acid, acid radical, and trivalent chromium, the chromic acid concentration is 300-400g / L, the acid radical concentration is 3.0-3.5g / L, the trivalent chromium concentration is 2-5g / L, the temperature is 60℃, the cathode current density is 25A / dm², and the time is 10-50 minutes; 3.4 High temperature baking treatment, the temperature is 350℃, the time is 3 hours, and then naturally cool.
4. The electroplating method according to claim 1, characterized in that: The dosage of the HT-57 titanium surface conditioner is 300 ml / L, the temperature is 40° C., and the time is 20 seconds.
5. The electroplating method according to claim 1, characterized in that: The dosage of agent A for the HT-79W titanium material special pre-nickel plating is 500ml / L, the dosage of agent B is 200ml / L, the pH value is 2.5, the time is 5 minutes, and the cathode current density is 3A / dm².
6. The electroplating method according to claim 2, characterized in that: In the chemical polishing process, the dosage of HT-678 chemical polishing agent is 250 ml / L, the processing temperature is 30° C., and the chemical polishing time is 1 minute; In the ultrasonic degreasing process, the dosage of HT-35F titanium degreasing agent is 100 g / L, the temperature is 60° C., the current density is 3 A / dm2, and the time is 2 minutes.
7. The electroplating method according to claim 2, characterized in that: In the cathode electrolytic degreasing treatment process, the amount of HT-35FA titanium degreasing agent is 80g / L, the temperature is 60°C, the current density is 3A / dm2, and the time is 2 minutes; In the acid etching process, 100 ml / liter of 68% nitric acid and 150 ml / liter of 40% hydrofluoric acid are used, and the treatment time at room temperature is 30 seconds.
8. The electroplating method according to claim 3, characterized in that: In the semi-gloss nickel electroplating process, the amount of semi-gloss nickel bath building agent MU used is 6-10 ml / L, the amount of semi-gloss nickel gloss agent used is 0.3-0.5 ml / L, and the amount of wetting agent used is 0.4-1.0 ml / L; In the glossy nickel electroplating process, the amount of nickel gloss agent used is 0.4-0.6 ml / L, the amount of nickel softener used is 6-10 ml / L, and the amount of nickel wetting agent used is 0.6-0.8 ml / L.
9. The electroplating method according to claim 3, characterized in that: In the chromium electroplating process, the amount of chromium additive used is 20-30 ml / L.
10. An electroplating material, characterized in that: The steel-titanium material is prepared by the electroplating method according to any one of claims 1 to 9.